Characterization and content analysis of Instagram posts about sports supplementation - Eisenhower de Araujo Santos; Clara Amelia Nunes de Oliveira; Maycon George Oliveira Costa; Róger Conceição Torres Junior; Luana Edla Lima; Marcus Vínicius Santos do Nascimento; Fabiana Poltronieri; Raquel Simoes Mendes-Netto (Instituto Brasileiro de Pesquisa e Ensino em Fisiologia do Exercício, 2024)
Supplementation in sports has become popular and social media plays an important role in facilitating access and speeding up the dissemination of health information to society. However, at the same time, supplements represent a significant exposure source to health misinformation, which can directly impact the health of individuals who consume this information. The objective of the study was to characterize and analyze the quality of content published on Instagram on the subject of sports supplementation. Thus, the top 10 posts on Instagram were collected from the search for key hashtags on the subject over 5 weeks, 2 times a week, and content analysis was quantitatively and qualitatively performed from the Descending Hierarchical Classification, word cloud and the DISCERN instrument. As a result, 112 posts composed the analyzed textual corpus, with mentions of 154 supplements; moreover, 39.4% of the authors were nutritionists, followed by content creators (23.2%) and nutrition students (16.9%), with greater female representation (66.9%), and the hashtag "supplementation" was responsible for 60.5% of the analyzed posts. The main themes present in the posts involve aspects of creatine supplementation, predetermining factors for supplementation, benefits and characteristics of protein supplementation. The average DISCERN score was 2.77, representing a low reliability of the posts; however, professionals and students in the nutrition area had higher averages. The results show that publications on the subject of sports supplementation have low quality of scientific reliability, but that quality may vary depending on the education level of the author of the publication.